Water Quality Index of the Tigris River in the Central of Iraq - Noor A. H. Alharbawee; Ahmed Jasim Mohammed; Wesam Mahmood (Journal of Techniques)
An attempt has been made to evaluate the water quality of the Tigris River in the central of Iraq. 13 physical and chemical factors were monitored at 5 monitoring stations from October 2021 to September 2022. Water quality index (WQI) technique, namely, the Bascaron Water Quality Index (BWQI) was used to explore the quality of the river, which is one of the most applied indices to assess the river's water quality. The result presented was that the WQI final values dropped from the north to the south gradually and were determined to be between 57.08 and 70. The Jisr Diyala station had the lowest WQI rating, while the Balad station had the greatest value. The water quality of the Tigris River in the study area has been classified as "medium" water quality according to BWQI. This is mostly caused by the increase of agricultural, domestic, and industrial activities that increase the amount of pollution in the river when the water is flowing southward.